2014
DOI: 10.1186/2193-1801-3-717
|View full text |Cite
|
Sign up to set email alerts
|

Practice of switch from intravenous to oral antibiotics

Abstract: Hospitalized patients initially on intravenous antibiotics can be safely switched to an oral equivalent within the third day of admission once clinical stability is established. This conversion has many advantages as fewer complications, less healthcare costs and earlier hospital discharge. The three types of intravenous to oral conversion include sequential, switch, and step-down therapy. The aim of the study was to evaluate the practice of switching from intravenous to oral antibiotics, its types and its imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 48 publications
3
49
1
3
Order By: Relevance
“…There are also doctors who prescribe switching based on the patient's clinical conditions, such that it is done earlier. Some studies suggest that the optimal time for switching is the 2 nd to 4 th day of intravenous antibiotics [6,15,16]. The study did not observe any patients who relapsed or required intravenous antibiotics again after switching.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…There are also doctors who prescribe switching based on the patient's clinical conditions, such that it is done earlier. Some studies suggest that the optimal time for switching is the 2 nd to 4 th day of intravenous antibiotics [6,15,16]. The study did not observe any patients who relapsed or required intravenous antibiotics again after switching.…”
Section: Resultsmentioning
confidence: 78%
“…However, the decrease in the length of hospitalization was not found to be statistically significant. A retrospective observational study in Lebanon [6] reported that the duration of intravenous antibiotics administered in the switching group was shorter than that in the nonswitching group. The length of hospitalization in the switching group was shorter than in the switching group, but these results were not significant either.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and possibly earlier discharge . A conservative estimate of 2 days saved of IV therapy is likely appropriate given the previous literature …”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
“…The pharmacokinetic profile is similar between oral and intravenous formulations, allowing for easy conversions between the formulations. However, antimicrobials are frequently delivered intravenously in hospitalized patients even if they are capable of taking oral medications [11]. Furthermore, the intervention for conversion of routes of administration to reduce the length of hospital stay and cost is not frequently performed in Korea.…”
Section: Discussionmentioning
confidence: 99%